Phylogeny and evolution of head shape in the Amphisbaenia (Reptilia: Squamata) - Mendes, Roberta Graboski (2018)
Within the Squamata, the suborder Amphisbaenia consists of a group of legless lizards that have adapted to fossorial life through several morphological changes. Currently, Amphisbaenia comprises 192 described species that are divided into six families (Amphisbaenidae, Blanidae, Bipedidae, Cadeidae, Rhineuridae, and Trogonophidae). The suborder is widely distributed, occurring in the Neotropical region, sub-Saharan Africa, parts of the Mediterranean region, Baja California and Florida. Despite advancements in the knowledge of the group, the phylogenetic position of Amphisbaenia within Squamata and the relationships among its families and genera remains uncertain. Many studies attribute the difficulties in understanding the origin and evolution of the Amphisbaenia to the convergence of the head shapes. Thus, the present study aims to investigate and contribute to fill these gaps in the knowledge of this group. For this, it was provided a new phylogenetic and taxonomic proposal for Amphisbaenia a combination of different approaches for taxon and character methods (Sanger, Anchored Phylogenomics and morphological data) to understand the relationships among families and genera, as well as to infer the phylogenetic position of the Amphisbaenia within Squamata. Additionally, this study aims to understand the evolution of head forms within Amphisbaenia, testing whether these forms have a phylogenetic or environment relationship, and if they are morphological convergences. High-resolution X-ray computed tomography (HRXCT), anatomical landmarks and geometric morphometrics techniques were used to analyze the differences in head shape of 135 species of Amphisbaenia